MENAFSIRKAN TEKS SASTRA LISAN BADAMPIANG SEBAGAI UPAYA MEMAKNAI WARISAN BUDAYA BANGSA - nfn Krisnawati (Madah: Jurnal Bahasa dan Sastra, 2016)
Minangkabau ethnic group, as other ethnic groups in Indonesia, has many kinds of cultural heritages. Among other is Badampiang, an oral tradition. Badampiang (acting of accompanying) is mutually responding poetry (berbalas pantun) by the time accompanying a groom to a bride’s house to do the procession of wedding. This tradition is currently threatened to extinct, whereas in fact, it has many positive values which are deserved to be inherited to the next generations. Thus, it is important to do a research on Badampiang. This paper discussed about the speakers, the music instruments, the place, the time and the condition of Badampiang utterances. Besides, this paper also discussed the meaning contained in the text of Badampiang. The method used to investigate the tradition of Badampiang is hermeneutics method and theory of values. Therefore, the various elements that exist can be found so that badampiang will realize and the values that contained in the oral tradition.